Evaluasi Kualitas Marketplace PT. Metraplasa (Blanja.com) Berdasarkan Kepuasan Pengguna, Kerangka Kerja Webqual 4.0, dan Importance Performance Analysis (IPA) - Nozomi Alifia Ghaisani; Admaja Dwi Herlambang; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Companies competition that engaged in the field of online trading was increasing especially in the development of e-commerce in Indonesia, they were competing to provide the best service and quality of the website for users to feel satisfied. Blanja.com is an online marketplace of e-commerce type. Blanja.com had aspect related issues of usability, information quality, service interaction quality. The purpose of this research is to show the scale of the priorities that appear then conducted research using quantitative approach. The population of this study is the total number of users who already have Blanja.com account (registered member) of 1.700.000 people and then selected a sample of 109 people by using convenience sampling. Data were collected by questionnaire. Conditions on variable usability, information quality, service interaction quality, and user satisfaction are in high categories at both performance and importance levels. Transaction and information security indicators are in quadrant A (concentrate here). Performance, timeliness, purchase satisfaction, and experience satisfaction indicators are in the C quadrant (low priority). The recommendations given for this research are to improve the quality of transaction and information security, performance, purchase satisfaction, and experience satisfaction.